Interaction of luminescent defects in carbon nanotubes with covalently attached stable organic radicals - Berger, Felix J.; de Sousa, J. Alejandro; Zhao, Shen; Zorn, Nicolas; El Yumin, Abdurrahman Ali; Quintana García, Aleix; Settele, Simon; Högele, Alexander; Crivillers, Núria; Zaumseil, Jana (ACS nano, 2021)
The functionalization of single-walled carbon nanotubes (SWCNTs) with luminescent sp3 defects has greatly improved their performance in applications such as quantum light sources and bioimaging. Here, we report the covalent functionalization of purified semiconducting SWCNTs with stable organic radicals (perchlorotriphenylmethyl, PTM) carrying a net spin. This model system allows us to use the near-infrared photoluminescence arising from the defect-localized exciton as a highly sensitive probe for the short-range interaction between the PTM radical and the SWCNT. Our results point toward an increased triplet exciton population due to radical-enhanced intersystem crossing, which could provide access to the elusive triplet manifold in SWCNTs. Furthermore, this simple synthetic route to spin-labeled defects could enable magnetic resonance studies complementary to in vivo fluorescence imaging with functionalized SWCNTs and facilitate the scalable fabrication of spintronic devices with magnetically switchable charge transport.